The Sufi Lexicon and Its Relationship to the Construction of Poetry - messaoudene, mohamed (El Omda in Linguistics and Discourse Analysis, 2025)
"This study explores the Sufi lexicon and its role in poetic construction, focusing on the lexical fields of wine terminology and mystical ranks. It examines how these lexicons guide the reader's interpretation despite the complexity of such encoded texts, while tracing the Sufi poem's progression from a simple concept to an existentially realized scriptural form."